Attacking styles for Tromsø IL- A study of goals and how Tromsø IL score goals. -An investigation for classifying goal scoring patterns and scoring efficiency. A case study of Tromsø Idrettslag. - Johansen, Jonas (UiT The Arctic University of Norway, 2021)
Abstract Attacking styles within Tromsø IL- A study of scored goals and how Tromsø IL score goals. The purpose of this study is finding what attacking styles and formation were most effective regarding scoring goals for Tromsø IL (TIL) in the competitive seasons 2018, 2019 and 2020. In total TIL have scored 140 goals over the three seasons which averages 46,6 goals per season. Analyses of which style of attack and playing formation shown to be most effective for TIL in scoring goals over the three seasons will be investigated. The study will look at different variables that could affect the efficiency in attack prior to goals scored. The aim of the research is to provide coaches with knowledge regarding goal scoring patterns in TIL and encourage the club to implement the findings in training and match strategy. Material and methods This study will use a quantitative method. Including (n=48) players and (n=140) goals. The variables that will be emphasized are attacking styles, passes prior to goal, formation, and goal box runs. Video analysis of match from different video resources and match statistics have been made available by Wyscout. I will use cross tables and figures to present the findings. To test the selection a Chi-Square test is used to check the observed frequency in relation to the expected frequency between variables based on the selection. The significance level was set to p<0.05. Findings: Results show that the most effective attacking pattern was possession attack. 47,8 % of goals were scored after a possession attack. The study also show that the goals defined as a goal box run was lowest in the relegation season 2019 with only (3) goals scored from a box runs, compared to 2018 (25) goals and 2020 (28) goals. The number of passes prior to goal is most effective when executing 0-3 passes. The most effective formation was the 3-5-2 formation which gave a goal every 35th minute. When investigating time syntax, the most effective periods were between 31-45 and 46-60 minutes. When TIL score first ...